Integrated analysis of lncRNA/circRNA–miRNA–mRNA in the proliferative phase of liver regeneration in mice with liver fibrosis - Wang, Qian; Long, Zhangtao; Zhu, Fengfeng; Li, Huajian; Xiang, Zhiqiang; Liang, Hao; Wu, Yachen; Dai, Xiaoming; Zhu, Zhu (BMC genomics, 2023)
Non-coding RNAs play important roles in liver regeneration; however, their functions and mechanisms of action in the regeneration of fibrotic liver have not been elucidated. We aimed to clarify the expression patterns and regulatory functions of lncRNAs, circRNAs, miRNAs, and mRNAs in the proliferative phase of fibrotic liver regeneration. Based on a mouse model of liver fibrosis with 70% hepatectomy, whole-transcriptome profiling was performed using high-throughput sequencing on samples collected at 0, 12, 24, 48, and 72 h after hepatectomy. Hub genes were selected by weighted gene co-expression network analysis and subjected to enrichment analysis. Integrated analysis was performed to reveal the interactions of differentially expressed (DE) lncRNAs, circRNAs, miRNAs, and mRNAs, and to construct lncRNA-mRNA cis- and trans-regulatory networks and lncRNA/circRNA-miRNA-mRNA ceRNA regulatory networks. Real-Time quantitative PCR was used to validate part of the ceRNA network. A total of 1,329 lncRNAs, 48 circRNAs, 167 miRNAs, and 6,458 mRNAs were differentially expressed, including 812 hub genes. Based on these DE RNAs, we examined several mechanisms of ncRNA regulatory networks, including lncRNA cis and trans interactions, circRNA parental genes, and ceRNA pathways. We constructed a cis-regulatory core network consisting of 64 lncRNA-mRNA pairs (53 DE lncRNAs and 58 hub genes), a trans-regulatory core network consisting of 103 lncRNA-mRNA pairs (18 DE lncRNAs and 85 hub genes), a lncRNA-miRNA-mRNA ceRNA core regulatory network (20 DE lncRNAs, 12 DE miRNAs, and 33 mRNAs), and a circRNA-miRNA-mRNA ceRNA core regulatory network (5 DE circRNAs, 5 DE miRNAs, and 39 mRNAs). These results reveal the expression patterns of lncRNAs, circRNAs, miRNAs, and mRNAs in the proliferative phase of fibrotic liver regeneration, as well as core regulatory networks of mRNAs and non-coding RNAs underlying liver regeneration. The findings provide insights into molecular mechanisms that may be useful in developing new therapeutic approaches to ameliorate diseases that are characterized by liver fibrosis, which would be beneficial for the prevention of liver failure and treatment of liver cancer.